Biocarvões de palha de café e casca de eucalipto produzidos a 350 e 600°C como condicionadores do solo - Silva, Ronaldo Willian da (2017)
Soil organic matter (SOM) is of great importance in the formation and maintenance of chemical, physical and biological properties of tropical soils and contributes up to 80 % of its cation exchange capacity (CEC). However, in tropical regions, the rate of